THE FORMATIVE VALUE OF THE TECHNOLOGICAL EDUCATION CURRICULUM CONCERNING THE PREADOLESCENT TRAINING FOR THE ROLE OF PARENTS RESPONSIBLE - ROTARU, Ioana Corina; OVCERENCO, Nadejda (Acta et Commentationes, Sciences of Education, 2020)
Technological education is a general culture discipline, which we consider a component of the basic culture and an action coordinate for lifelong learning. By introducing the technological education discipline into the super-technological society, it leads to the cultivation of technological humanism and the formation of an attitude of responsibility and high morality. From a qualitative point of view, technological education contributes to the formation of a generation with real inclinations towards initiative, creativity, cooperation that lead to learning to do well.